2021
DOI: 10.1021/acsnano.1c08619
|View full text |Cite
|
Sign up to set email alerts
|

Nanotransferrin-Based Programmable Catalysis Mediates Three-Pronged Induction of Oxidative Stress to Enhance Cancer Immunotherapy

Abstract: Current oxidative stress amplifying strategies for immunogenic cell death (ICD) promotion are mainly restricted to immune tolerance induced by adaptive cellular antioxidation, limited tumor-selectivity, and tumoral immunosuppression. Herein, a facile and efficient scenario of genetically engineering transferrin-expressing cell membrane nanovesicle encapsulated IR820-dihydroartemisinin nanomedicine (Tf@IR820-DHA) was developed to boost a-PD-L1mediated immune checkpoint blocking (ICB) via synergetic triple stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 49 publications
(67 reference statements)
0
51
0
Order By: Relevance
“…In recent years, studies based on biodegradable nanomaterials have shown that the inherent anti-cancer activity can be regulated by disturbing the intracellular ion balance due to the related biological activity of their degradation products, which is known as ion interference therapy (IIT) [ 110 , 111 ]. Of these aspects, iron-based materials (“ferroptosis”) [ 112 114 ] and sodium chloride [ 115 , 116 ] provided the good demonstration. Therefore, ion-interfering cancer therapy is expected to become a new therapeutic tool as a supplement to traditional clinical cancer therapy.…”
Section: Calcium-based Nanomaterials For Cancer Diagnosis and Therapymentioning
confidence: 99%
“…In recent years, studies based on biodegradable nanomaterials have shown that the inherent anti-cancer activity can be regulated by disturbing the intracellular ion balance due to the related biological activity of their degradation products, which is known as ion interference therapy (IIT) [ 110 , 111 ]. Of these aspects, iron-based materials (“ferroptosis”) [ 112 114 ] and sodium chloride [ 115 , 116 ] provided the good demonstration. Therefore, ion-interfering cancer therapy is expected to become a new therapeutic tool as a supplement to traditional clinical cancer therapy.…”
Section: Calcium-based Nanomaterials For Cancer Diagnosis and Therapymentioning
confidence: 99%
“…Bergdorf et al demonstrated that dendritic cells and neutrophils could promote lymph node (LN) metastasis and affect prognosis through the LAG3-mediated immunosuppression in PTCs [ 11 ]. The latest ICB synergetic triple stimuli-activated nanoimmunotherapy has represented that more potential immune regimens effectively improved the overall response of cancer patients [ 12 ]. In summary, ferroptosis-associated lncRNAs have significant potential to become prognostic assessment markers and provide immunotherapeutic strategies for TC.…”
Section: Introductionmentioning
confidence: 99%
“…Healthy embryos of 72 hpf (melanin formation) were randomly selected under a continuous magnification microscope using the plastic dropper. 38,39 A 6-well cell culture plate was used as the experimental carrier, and 30 embryos were added into each well. After the culture water was dried with a plastic pipette, 5.0 mL of the diluent prepared from the test sample was added to each well (5 concentrations) of the 6-well cell culture plate above.…”
Section: Inhibition Of Melanin Formation By Antioxidants At Different...mentioning
confidence: 99%